THE INFLUENCE OF THE PRINCIPAL’S LEADERSHIP ROLE, RELIGIOUS CUSTOMIZATION AND CHARACTER EDUCATION PROGRAMS ON THE WORK CLIMATE IN MADRASAH TSANAWIYAH, BANJARBARU - Perdana, Sativa; Ahmad Suriansyah; Ngadimun (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
The achievement associated with educational goals is inseparable from a conducive school environment that helps to create a feeling of comfort in educational institutions. This study aimed to determine the role of principal leadership, religious habituation programs, character education, and work climate in Madrasah Tsanawiyah, Banjarbaru City. This was a quantitative study that utilized correlational techniques through path analysis with a total sample of 173 people. Data were collected by using questionnaires that have met the validity and reliability test requirements, with path analysis and multiple regression methods used to test the hypotheses. The results showed that the leadership role of school principals, the religious habituation program, character education, and work climate in madrassas were of high classification. This led to the creation of leadership that was able to advance schools with good characters.